2021
DOI: 10.1093/sleep/zsab186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total sleep deprivation and related mood changes on approach-avoidance decisions to threat-related facial displays

Abstract: Study Objectives Total sleep deprivation is known to have significant detrimental effects on cognitive and socio-emotional functioning. Nonetheless, the mechanisms by which total sleep loss disturbs decision-making in social contexts are poorly understood. Here, we investigated the impact of total sleep deprivation on approach/avoidance decisions when faced with threatening individuals, as well as the potential moderating role of sleep-related mood changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 98 publications
(112 reference statements)
7
25
0
Order By: Relevance
“…Findings of a stress test simulating a military march also supported the contention that one-night sleep deprivation presents no obvious effects on physical and physiological responses ( Nieto-Jiménez and Orellana, 2020 ). Moreover, deprivation of sleep has been known to affect brain functions ( Patrick et al, 2017 ; Hudson et al, 2020 ; Garbarino et al, 2021 ; Grèzes et al, 2021 ). In addition, recent studies reported a decrease in respiratory motor output by altering its cortical component with a subsequent reduction of inspiratory endurance while being deprived of one-night sleep ( Westphal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings of a stress test simulating a military march also supported the contention that one-night sleep deprivation presents no obvious effects on physical and physiological responses ( Nieto-Jiménez and Orellana, 2020 ). Moreover, deprivation of sleep has been known to affect brain functions ( Patrick et al, 2017 ; Hudson et al, 2020 ; Garbarino et al, 2021 ; Grèzes et al, 2021 ). In addition, recent studies reported a decrease in respiratory motor output by altering its cortical component with a subsequent reduction of inspiratory endurance while being deprived of one-night sleep ( Westphal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We suggested that such an influence was mediated by the fact that threat displays increased the value of the action leading to avoidance (Vilarem et al, 2020). We revealed that avoidance decisions did indeed result from rapid and implicit value-based competition between action alternatives, a mechanism sourced in the ventromedial prefrontal and the orbital cortices (Mennella et al, 2020; for a conceptual replication see Buades-Rotger et al, 2021) and modulated by changes in participants' positive affective state (Grèzes et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…The main task (Fig. 1) was adapted from previous studies (Grèzes et al, 2021;Mennella et al, 2020;Vilarem et al, 2020).…”
Section: Reinforcement Learning Taskmentioning
confidence: 99%
See 2 more Smart Citations